Transparansi Digital dan Loyalitas Donatur: Strategi Mitigasi Risiko Program Filantropi Islam : (Studi Kasus LAZIS Alharomain Pare Kediri) - Lulud Wijayanti; Siti Nurjanah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze how digital transparency, distribution validation, and personalized donor services simultaneously maintain donor trust and loyalty as strategies to mitigate liquidity risk and ensure program sustainability at LAZIS Alharomain Pare Kediri Branch. Using a qualitative descriptive–analytical approach, data were collected through in-depth interviews, observation, and documentation involving management, donors, and beneficiaries. The findings reveal a paradox between the increasing number of donors—from 5,644 in 2020 to 7,955 in 2023—and the financial deficit observed in key programs such as Infaq Sayangi Anak Yatim Dhuafa and Infaq Sahabat Sehat. To address this, the institution implemented three main strategies: real-time digital reporting via social media, multi-layered verification in fund distribution, and personalized communication with donors. These strategies form a trust–loyalty–participation cycle that strengthens program continuity. Theoretical analysis based on Trust Theory and liquidity risk management for zakat institutions shows that public trust functions as a form of social capital capable of compensating for short-term financial liquidity gaps. This study extends the discourse on Sustainable Islamic Philanthropy Governance by asserting that digital transparency serves as both an ethical and strategic instrument to uphold accountability and the sustainability of Islamic philanthropic institutions.